Assumption, the mother of all foul ups: a fundamental reason for the continuing abuse of adults at risk. Issue 3 (13th August 2018) - Moore, Steve
Abstract : Purpose: The purpose of this paper is to introduce the concept of the assumption of altruism argued by the author to be a tendency among both the lay public, professionals and politicians, a generalised assumption that contributes to the long standing and obstinate presence of abuse of adults who are at risk throughout England, particularly older people living in care and nursing homes. Design/methodology/approach: By examining available figures that depict the continuing abuse of vulnerable adults, and by drawing on research, the author offers a partial explanation for the longevity of abuse in English society. Findings: The paper demonstrates how the concept of the assumption of altruism can explain to a degree the apparent enduring levels of abuse of adults who are at risk. Practical implications: The paper offers the opportunity for the reader to consider some of the fundamental, higher order reasons for the persistent levels of abuse in England, abuse that endures despite the oversight by government of care provided to adults who maybe at risk by virtue of the activities of the statutory regulator and health and social care commissioners. Originality/value: By presenting the incontrovertible evidence of enduring abuse, the paper introduces the concept of the assumption of altruism as a partial explanation for its continuing occurrence despite decades of policy and practice guidance designed to overcome it.